The Role of Information Systems in Improving the Efficiency of Business Decision Making - Nisrina, Sefiyana Jihanuri; Masviansyah, Reihan; Adiwana, Andrew Wijaya; Kusumasari, Indah Respati; Hidayat, Rusdi (Indonesian Journal Publisher, 2025)
Information system is one of the important aspects in decision making by business people. This study aims to analyze how much impact information systems have on the decision-making process in the business environment. By combining information technology, companies can process their data effectively and efficiently and increase accuracy in data analysis. In addition, information systems can be an alternative strategy that is fast and thorough in the decision-making process. The results of this study show that implementing a good information system can speed up the decision-making process, improve the accuracy of data analysis, and enable companies to respond to market changes more quickly and precisely. Information systems also help in processing big data, which provides deep insights for managers in making strategic decisions.